Pengaruh Kualitas Layanan dan Hubungan Pelanggan terhadap Loyalitas Konsumen Shopee di Desa Citimun Kecamatan Cimalaka Sumedang - Shelly Nur Fajrianti Rahayu; Evi Sofiati (Journal of Economic and Business Advancement, 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among digital platforms, making customer loyalty a crucial strategic asset. This study aims to analyze the effect of service quality and customer relationship on Shopee consumer loyalty in Citimun Village, Cimalaka District, Sumedang Regency. A quantitative approach with an associative and explanatory research design was employed. The results indicate that service quality significantly influences consumer loyalty through reliable systems, ease of transactions, and consistent service performance. In addition, customer relationship management plays an important role in strengthening emotional attachment and trust, which encourages repeat purchases and long-term platform usage. This study provides empirical evidence that service quality and customer relationship are key determinants of e-commerce loyalty, particularly in rural areas that are still underrepresented in previous research.